Full-scale experimental study on stress deformation of large diameter natural gas pipeline in subsidence area - Wen WANG; Lei HONG; Jiandong REN; Xiaowei LU; Shuang GONG; Runsheng GUO; Miao DONG (Meitan xuebao)
To investigate the mechanical characteristics and deformation evolution patterns of buried natural gas pipelines under subsidence in coal and natural gas overlapping areas, this study integrates pipeline deformation theory with numerical simulation to analyze the effects of mining-induced subsidence on pipeline deformation. Moreover, full-scale mechanical characteristic tests were conducted to explore the stress and deformation behavior of large-diameter pipelines under external loads, followed by a comprehensive safety and operation analysis. The results demonstrate that, as pipeline subsidence increases, the amount of subsidence at the pipeline ends is smaller than the central segment, and the deformation is approximately symmetrically distributed around the center. The relative displacement at the center of the pipeline is less than that at the ends. Under the combined effects of self-weight and external load, the top of the pipeline is subjected to compressive forces, while the bottom experiences tensile forces. The compression and tensile deformation increase progressively from the ends toward the center, with the maximum deformations occurring at the pipeline center. As the applied load increases, the overall deformation pattern of the pipeline transitions from a flat-bottom shape to a funnel-like shape. Under self-weight, the maximum settlement of the pipeline is 45 cm, reaching 35% of the maximum allowable settlement. When external loads are applied, the maximum settlement increases to 63.6 cm, accounting for 50% of the maximum allowable settlement. Based on the pipeline’s tensile strain and the maximum allowable elastic deformation, the safety threshold of the pipeline was estimated. The tensile displacements were calculated as 31 mm and 90 mm under coordinated and uncoordinated deformations between the pipeline and surrounding soil, respectively, which remain below the material’s safety limits.